Development of information technology to optimize the speed of a steam generator control system with the identification of nonlinear models - Nikulina, Olena; Severyn, Valerii; Kotsiuba, Nina; Pashniev, Andrii; Usyk, Andrii (Eastern-European Journal of Enterprise Technologies, 2025)
This study’s object is the process that controls water level in steam generator at a nuclear power plant. The task considered is to optimize the speed of operation and automatic control system of the steam generator. Optimization information technology for water level control system in steam generator has been proposed, based on nonlinear mathematical models and level objective functions. Nonlinear mathematical model of control system has been considered, which is built to optimize quality indexes of the system. Applying the developed algorithms, computational experiments were performed to identify and optimize parameters of control system by optimizing level objective functions. Values for 41 parameters in the model of a water level control system in PGV-1000 steam generator were determined. The resulting value for mean square deviation of the model’s processes from experimental ones equals 0.43%, which is 54% less than when using linear model. As a result of optimizing water level control system when load is dropped by 20%, a minimum control time of 146 s was achieved. A change in the water level in a steam generator did not exceed 24% of maximum allowable value. A special feature of the devised optimization information technology for control system is that the level objective function includes all information about optimization problem of a nonlinear control system. This simplifies algorithms and software for solving optimization problems in complex control systems. The technology for optimizing nonlinear control systems considered here could make it possible to increase degree of scientific validity of technical projects for improving various applied and promising control systems